LOCAL ECONOMIC STRENGTHENING THROUGH ENVIRONMENTALLY FRIENDLY ENERGY UTILIZATION: BILATERAL COOPERATION FOR SUSTAINABLE COASTAL COMMUNITY DEVELOPMENT - Annisa Ilmi Faried; Dian Septiana Sari; Rahmad Sembiring; Saimara Sebayang; Nor Harlinda Binti Harun; Nisa Ulzannah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This community service initiative explores the implementation of sustainable energy solutions to enhance local economic development in coastal areas through Indonesia-Malaysia bilateral cooperation. The program focuses on integrating renewable energy systems with community-based economic activities, emphasizing solar panels, micro-hydro installations, and biomass conversion technologies. The methodology involves participatory action research with 150 coastal households across three villages, implementing energy-efficient technologies while establishing micro-enterprises. Results demonstrate significant improvements in household income levels, with average increases of 45% over 18 months. The bilateral collaboration facilitated knowledge transfer, technical expertise sharing, and joint funding mechanisms. Environmental benefits include 30% reduction in carbon emissions and enhanced coastal ecosystem preservation. The program successfully established 25 new micro-businesses, created 80 direct employment opportunities, and improved energy access for 450 community members. This model demonstrates effective integration of environmental sustainability with economic empowerment through international academic partnerships, providing replicable frameworks for similar coastal development initiatives across Southeast Asian regions.